Pelatihan Media Digital Bagi Kader Posyandu Merah Delima Lok Bahu - Pradita, Adelia Putri; Maulana, Ady; Fitriani, Ananda Aulia Cahya; Pramesti, Elviana Emilda Dyah; Aulia, Farah; Kurniawan, Haura Tamara Karin; Rizqi, Jennisa; Sariyati, Mely; Saputra, Ra’azi; Wijayanti, Siti Choirul Jannah Dewi; Permana, Lies; Rohmah, Nur; Agustini, Rina Tri; Nurrachmawati, Annisa (Lembaga Dongan Dosen, 2025)
Posyandu Merah Delima is an infant and toddler posyandu located in Lok Bahu Village, Samarinda City. After conducting a Focus Group Discussion (FGD) with the USG (Urgency, Seriousness, Growth) method, it was found that the problem of low compliance of mothers of infants and toddlers in bringing Maternal and Child Health (MCH) books and low participation during posyandu activities took place. To overcome this problem, cadres were empowered through training in the use of digital technology with a focus on making alternative MCH book forms using Canva and Microsoft Word applications and training in the Google Calendar application as a reminder for posyandu visits. The results showed an increase in knowledge and skills of posyandu cadres in making forms and reminder media using modern digital technology. The program also succeeded in encouraging the active involvement of cadres in planning and implementing activities, and strengthening the role of posyandu as a means of supporting the health of children under five in a sustainable manner.